Listening Anxiety among Undergraduate EFL Students - Adinda Mutiara Maharani; Dewi Warna; Sartika, Eka (Corolla International Conference, 2023)
The aim of this study was to determine the level of students' anxiety and the factors that cause students' anxiety in listening. The participants in this study were sixth semester EFL students at UIN Raden Fatah Palembang. This study used mixed methods with a sequential explanatory design. To find out the level of students' anxiety in listening, scores obtained from students' responses to the items on the Foreign Language Listening Anxiety Scale (FLLAS) and student scores were analyzed using descriptive statistical analysis. Meanwhile, to find out the factors that cause students' anxiety in listening, the data obtained from the interviews were analyzed using thematic analysis. The results showed that the students' anxiety level was 86.9% moderate level, 11.9% high level, and 1.2% low level of anxiety in listening. The findings show that students' anxiety level is influenced by background knowledge, text aspect and listening strategy, and listeners' characteristics. Five factors were also found that made students anxious in listening: 1) tension and worry; 2) lack of confidence; 3) lack of focus attention; 4) difficulty understanding foreign words; 5) speaker speaking speed.